The Importance of Eating Behavior in Eating Disorders - Walsh, B. Timothy (2011)
A disturbance in eating behavior is the defining characteristic of the clinical eating disorders, Anorexia Nervosa, Bulimia Nervosa, and Binge Eating Disorder. Surprisingly little research has been devoted to assessing objectively the nature of the eating disturbances in these disorders, to elucidating what factors contribute to the development and persistence of these disturbances, or to describing how they change with treatment. This review, which is based on a Mars lecture delivered at the 2010 meeting of the Society for the Study of Ingestive Behavior, reviews objective information about the nature of the disturbances of eating behavior in eating disorders. These data suggest that more detailed knowledge of eating behavior is an essential component of a full understanding of eating disorders and may provide a foundation for studies of pathophysiology and for the development of new treatment methods.